Unusual Fatal Bitemporal Crushing Head injury By Industrial Baler Machine - Kumar, Pannag S; Sapeco , Silvano Dias (Journal of Indian Academy of Forensic Medicine, 2014)
A peculiar case of crushing head injury is presented, which was caused by compression of the head by a machine known as “Industrial Baler”, which is used for compressing and packing scrap. Most cases of head injury are caused by “acceleration-deceleration” or “direct impact” forces, and crushing head injuries are relatively fewer in frequency of occurrence. Also, amongst the cases of crushing head injury, most cases involve both dynamic and static forces acting on the head. This case is peculiar in the sense that only “pure-static” forces were involved. The pattern of scalp and vault injuries also was unusual as although caused by compression by a blunt flat object having a large surface area, the appearance was that of injuries caused by impact by a heavy, cutting (chopping) edged object. In jobs that require working with any sort of industrial machinery, there is a potential risk of injuries or death of workers handling them in the event of an accident so workers need to ensure that they operate the machine in only the correct manner and do not bring their bodies in close proximity to heavy machinery,